Psychosocial problems among the school children of working and non- working mothers - Koirala, P; Subba, R; Lopchan, M (Journal of Chitwan Medical College, 2017)
Adolescence is the period in human development during which several dramatic changes at biological, social, psychological and cognitive levels take place. The objective of this study was to find out psychosocial problems among school children of working and non-working mothers. A descriptive comparative research design and Probability Stratified Random sampling technique was applied in which 120 (60 working and 60 non working mothers’) school students of grade 9 and 10 selected from two Government Higher Secondary Schools of Bharatpur. Structured questionnaire and Youth Pediatric Symptoms Checklist-17 (YPSC-17) were administered. Data was analyzed by using IBM SPSS version 20 and Mean, Standard Deviation, t-test and chi-square test were applied. This study showed that school children of non working mothers’ (11.7%) had slightly more psychosocial problems than working mothers’ (8.3%). Male respondents of non working mothers experienced more psychosocial problems (29.4 %) than female (4.7%). Prevalence of psychosocial problems was found among school children of both working and non working mothers but there is no association between the psychosocial problems and employment status of mothers. Thus maternal employment status is not the exclusive reason behind the development of psychosocial problems among school children.